Enhancement Of Traffic Collision Avoidance Using Token Bucket Algorithm - Mat Nawi, Nor Afifah (UTeM, 2016)
Traffic collision is one of the problems that occur in the wired network. In order to provide a high performance network, QoS is required. Traffic shaping is one of the tools to provide QoS in the network traffic. However, implement the basic mechanism of traffic shaping cannot solve the issued. In this project, the optimal size of bucket in Token Bucket Algorithm is used as one of the techniques in traffic shaping. The variables of this algorithm is modified in order to offer the effective proposed token bucket size that can be used in wired network. Then, this project will be tested using OPNET modeler.